A time course study of glucose levels and innate immune response in gilthead seabream (Sparus aurata L.) after exposure to clove oil-eugenol derived anaesthetic. Issue 77 (June 2018) - Bahi, A.; Guardiola, F.A.; Esteban, M.A.
Abstract: Clove oil is used as an anaesthetic for many species of fish worldwide; however, relatively few studies have assessed its effects on the innate immune response on these species. The present work aimed to investigate the effects of clove oil-eugenol derived anaesthetic on some humoral and cellular immune response in gilthead seabream ( Sparus aurata L.). To compare with an unexposed control group, fish were exposed to 55 ppm clove oil for 5 min, before being sampled at 1, 24 and 48 h post-exposure. Serum glucose level was also measured to obtain information on the fish physiological response after clove oil anaesthesia. One hour after exposure the haemolytic complement activity of fish was lower than in the unexposed group. By contrast, the leucocyte peroxidase activity in head-kidney was significantly stimulated 24 h after exposure to clove oil-eugenol. The rest of innate immune parameters evaluated and the glucose levels not were affected by clove oil exposure at any sampling point. Overall, the use of clove oil at 55 ppm as anaesthetic did not seem to alter the innate immune response and neither did it trigger a stress response. The use of clove oil-eugenol derived had become common practice in aquaculture, and its use with gilthead seabream can be considered safe as it does not cause immunodepression in anesthetized fish. Highlights: Few studies have assessed the clove oil effects on the immune status. Glucose levels and immunity were evaluated in gilthead seabream after clove oil anaesthetic exposure. Glucose levels and the main immune parameters measured were not altered by 55 ppm clove oil exposure. Only the haemolytic complement activity was reduced in fish sampled after 1 h of clove oil exposure. Clove oil seems not to compromise the physiological and immune status in gilthead seabream.